2015
DOI: 10.1136/annrheumdis-2014-206578
|View full text |Cite
|
Sign up to set email alerts
|

Synovial CD4+ T-cell-derived GM-CSF supports the differentiation of an inflammatory dendritic cell population in rheumatoid arthritis

Abstract: ObjectiveA population of synovial inflammatory dendritic cells (infDCs) has recently been identified in rheumatoid arthritis (RA) and is thought to be monocyte-derived. Here, we investigated the role and source of granulocyte macrophage-colony-stimulating factor (GM-CSF) in the differentiation of synovial infDC in RA.MethodsProduction of GM-CSF by peripheral blood (PB) and synovial fluid (SF) CD4+ T cells was assessed by ELISA and flow cytometry. In vitro CD4+ T-cell polarisation experiments were performed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 49 publications
0
60
0
1
Order By: Relevance
“…However, it was shown that the abundance of IL-7 in RA joints plays a critical role in overcoming PD-1-mediated inhibition of T cells, leading to the prevalence of T-activating effects [164,165]. Furthermore, GM-CSF produced by synovial CD4 þ T cells supported the differentiation and activation of infDC, thus promoting a local inflammatory amplification loop [166]. In T1D, a protective role of TLR2 deficiency was described in NOD mice [167].…”
Section: Cdc Activationmentioning
confidence: 99%
“…However, it was shown that the abundance of IL-7 in RA joints plays a critical role in overcoming PD-1-mediated inhibition of T cells, leading to the prevalence of T-activating effects [164,165]. Furthermore, GM-CSF produced by synovial CD4 þ T cells supported the differentiation and activation of infDC, thus promoting a local inflammatory amplification loop [166]. In T1D, a protective role of TLR2 deficiency was described in NOD mice [167].…”
Section: Cdc Activationmentioning
confidence: 99%
“…CD4 + T cell-secreted GM-CSF was required for the generation of monocyte-derived inflammatory dendritic cells (infDCs) and disease progression for acute inflammatory arthritis and peritonitis in mice [30]. In human rheumatoid arthritis (RA), synovial CD4 + T cells were found to be a major source of GM-CSF that strongly promoted infDC differentiation [31]. In juvenile idiopathic arthritis, the frequency of GM-CSF-producing CD4 + T cells in synovial fluid was significantly correlated with GM-CSF protein level as well as serum erythrocyte sedimentation rate, an indicator of inflammation [32].…”
Section: Th Cell-derived Gm-csf In Autoimmune Neuronal Diseasementioning
confidence: 99%
“…Noster et al further demonstrated that human memory CD4 + T cells cultured in the presence of IL-1β and IL-23 do not induce GM-CSF compared to IL-12p70 alone (Noster et al, 2014). In humans, high levels of GM-CSF have been documented in RA and multiple sclerosis (Noster et al, 2014, Reynolds et al, 2015. Duhen et al reported the synergy between IL-1β and IL-12p70 induced high levels GM-CSF from human Th17 cells (Duhen and Campbell, 2014).…”
Section: Cells Nk Cells DC Macrophages B Cells and Keratinocytes mentioning
confidence: 99%
“…Indeed, Noster et al and Reynolds et al demonstrated that GM-CSF production by reactivated memory CD4 + T cells was suppressed by IL-1β, IL-6 or IL-23; while IL12p70 significantly enhanced GM-CSF production (Noster et al, 2014, Reynolds et al, 2015.…”
Section: P a G Ementioning
confidence: 99%
See 1 more Smart Citation